Brand Ambassadors, Brand Trust, and Hedonic Motivation in Shaping G2Glow Purchase Decisions - Rahma, Alma Syifa; Putri, Fuzha Melyani; Khomairo, Ratu Dini; Tinnafsiyyah, Nurfithroh; Zulaeka, Almira (Lentera Ilmu Nusantara, 2025)
This study explores the influence of Social Brand Ambassadors on purchasing decisions for G2Glow products, with Brand Trust as a mediating variable and Hedonic Motivation as a moderating variable. The aim of this research is to determine the extent to which brand ambassadors shape brand trust and how it affects consumer decision-making. A quantitative approach was employed using Partial Least Square (PLS) analysis, and data were collected from 101 respondents via an online questionnaire. The results indicate that Social Brand Ambassadors do not have a direct effect on purchasing decisions but do have a significant indirect effect through Brand Trust. Furthermore, Hedonic Motivation also has a significant influence on purchasing decisions. The analysis of variables reveals that Brand Trust plays a crucial role as a bridge between brand ambassadors and purchasing decisions, while Hedonic Motivation enhances the emotional influence in the buying process. The conclusion of this study highlights that brand trust is a key factor in influencing purchasing decisions, and the strategic use of the right brand ambassador can strengthen that trust. The originality of this study lies in integrating social brand ambassadors, brand trust, and hedonic motivation within a single model, offering a more comprehensive explanation of consumer behavior in the beauty industry. Theoretically, the findings extend consumer behavior and branding literature by showing that emotional and trust-based mechanisms are stronger predictors of purchasing decisions than ambassadorial presence alone, thereby contributing new insights into the role of mediated and moderated pathways in digital marketing contexts. The practical implication is that marketers should emphasize emotional elements and credibility in their promotional strategies.